Variability among Indian isolates of Fusarium oxysporum f. sp. lentis causing wilt in lentil - Hiremani, Neelakanth S; Dubey, S C (Indian Journal of Plant Protection, 2020)
Wilt is one of the most important diseases of lentil caused by Fusarium oxysporum f. sp. lentis (Fol). Seventy five isolates of the pathogen representing 7 different lentil growing states of India were characterised for their morphological characters and aggressiveness. The isolates exhibited variability in colony characters and conidia size. The colony colour varied from white to purple with the most common being white for 40 isolates. Fluffy texture (52 isolates) of the colony was predominant over appressed type (23). The microconidia size varied from 5.3 - 14.8×1.3 - 5.2 μm whereas, macro conidia were 14.3 - 46.5×2.5 - 5.1 μm in size, smallest being FLS 51 (14.3×2.5 μm) and FLS 36 largest (46.5×4.7 μm). Based on the growth rate (mm/day), the isolates were categorized into slow (up to 5 mm/day), medium (>5 to 6 mm/day) and fast (>6 mm/day) growing and the maximum isolates were in third group i.e. fast growth rate (32 isolates) followed by medium (22) and slow (21) growth rates. The Fol isolates were highly variable in their aggressiveness on the susceptible cultivar Sehore 74-3 and caused wilt incidence from20 to 80 per cent. Based on wilt incidence, the isolates were categorised into four groups. The highly aggressive (>50% wilt) group included the highest number of isolates (29) followed by moderately pathogenic group (>20 to 50% wilt) with 21 isolates.